Comparative study of differentiating human pluripotent stem cells into vascular smooth muscle cells in hydrogel-based culture methods - Qing Liu; Zhen Liu; Hongyu Gu; Yuxia Ge; Xuesheng Wu; Fuxing Zuo; Qian Du; Yuguo Lei; Zhanqi Wang; Haishuang Lin (Regenerative Therapy, 2023)
Vascular smooth muscle cells (VSMCs), which provides structural integrity and regulates the diameter of vasculature, are of great potential for modeling vascular-associated diseases and tissue engineering. Here, we presented a detailed comparison of differentiating human pluripotent stem cells (hPSCs) into VSMCs (hPSCs-VSMCs) in four different culture methods, including 2-dimensional (2D) culture, 3-dimensional (3D) PNIPAAm-PEG hydrogel culture, 3-dimensional (3D) alginate hydrogel culture, and transferring 3-dimensional alginate hydrogel culture to 2-dimensional (2D) culture. Both hydrogel-based culture methods could mimic in vivo microenvironment to protect cells from shear force, and avoid cells agglomeration, resulting in the extremely high culture efficiency (e.g., high viability, high purity and high yield) compared with 2D culture. We demonstrated hPSC-VSMCs produced from hydrogel-based culture methods had better contractile phenotypes and the potential of vasculature formation. The transcriptome analysis showed the hPSC-VSMCs derived from hydrogel-based culture methods displayed more upregulated genes in vasculature development, angiogenesis and blood vessel development, extracellular matrix compared with 2D culture. Taken together, hPSC-VSMCs produced from hydrogel-based culture system could be applied in various biomedical fields, and further indicated the suitable development of alginate hydrogel for industrial production by taking all aspects into consideration.